Analysis of the magnetically induced current density of molecules consisting of annelated aromatic and antiaromatic hydrocarbon rings. Issue 23 (31st May 2016) - Sundholm, Dage; Berger, Raphael J. F.; Fliegl, Heike
Abstract : The aromatic pathway of molecules with annelated aromatic and antiaromatic rings has been studied by calculating magnetically induced current densities. Abstract : Magnetically induced current susceptibilities and current pathways have been calculated for molecules consisting of two pentalene groups annelated with a benzene (1 ) or naphthalene (2 ) moiety. Current strength susceptibilities have been obtained by numerically integrating separately the diatropic and paratropic contributions to the current flow passing planes through chosen bonds of the molecules. The current density calculations provide novel and unambiguous current pathways for the unusual molecules with annelated aromatic and antiaromatic hydrocarbon moieties. The calculations show that the benzene and naphthalene moieties annelated with two pentalene units as in molecules1 and2, respectively, are unexpectedly antiaromatic sustaining only a local paratropic ring current around the ring, whereas a weak diatropic current flows around the C–H moiety of the benzene ring. For1 and2, the individual five-membered rings of the pentalenes are antiaromatic and a slightly weaker semilocal paratropic current flows around the two pentalene rings. Molecules1 and2 do not sustain any net global ring current. The naphthalene moiety of the molecule consisting of a naphthalene annelated with two pentalene units (3 ) does not sustain any strong ring current that is typical for naphthalene. Instead, half of the diatropic current passing the naphthalene moiety forms a zig-zag pattern along the C–C bonds of the naphthalene moiety that are not shared with the pentalene moieties and one third of the current continues around the whole molecule partially cancelling the very strong paratropic semilocal ring current of the pentalenes. For molecule3, the pentalene moieties and the individual five-membered rings of the pentalenes are more antiaromatic than for1 and2 . The calculated current patterns elucidate why the compounds with formally [4 n + 2] π-electrons have unusual aromatic properties violating the Hückel π-electron count rule. The current density calculations also provide valuable information for interpreting the measured 1 H NMR spectra.